PENGARUH PENGGUNAAN LEMBAR KERJA ANAK (LKA) BERBASIS CANVA TERHADAP MOTORIK HALUS ANAK DI TK NEGERI PEMBINA BARAT PAYAKUMBUH - Luthfiya Syalsaniyya sania; Dr. Nenny Mahyuddin, M.Pd (JCE (Journal of Childhood Education), 2025)
This article presents findings from a study focused on the fine motor skills of children aged 5 to 6 years, highlighting instances where these skills do not align with developmental norms. The primary objective of the research was to evaluate the impact of Canva-based worksheets on the fine motor skills of children at State Kindergarten Pembina Barat in Payakumbuh. To achieve this, an experimental method was employed, utilizing a quantitative quasi-experimental approach. The study consisted of a population that included all children enrolled in the West Pembina State Kindergarten, with Class B8 designated as the experimental group and Class B7 serving as the control group. Each group included 10 children, allowing for a comparative analysis of outcomes.Various data analysis techniques were utilized, including normality tests, homogeneity tests, and hypothesis tests, to assess changes in the fine motor skills of the children before and after the intervention. The results indicated that the average pre-test score for the experimental class was 20. 5, while the control group scored an average of 21. 1. In the post-test phase, the experimental class achieved an average score of 34. 7, compared to 28. 8 for the control class.Statistical analysis revealed a significant difference between the two groups, with the experimental class outperforming the control class by 5. 9 points in the post-test. These findings suggest that Canva-based worksheets are effective in enhancing fine motor skill development among children at the West Pembina State Kindergarten in Payakumbuh.